2005
DOI: 10.1038/sj.hdy.6800748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gene flow on spatial genetic structure in the riparian canopy tree Cercidiphyllum japonicum revealed by microsatellite analysis

Abstract: Few studies have analyzed pollen and seed movements at local scale, and genetic differentiation among populations covering the geographic distribution range of a species. We carried out such a study on Cercidiphyllum japonicum; a dioecious broad-leaved tree of cool-temperate riparian forest in Japan. We made direct measurement of pollen and seed movements in a site, genetic structure at the local scale, and genetic differentiation between populations covering the Japanese Archipelago. Parentage analysis of see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 33 publications
2
64
1
3
Order By: Relevance
“…Indeed, even in a highly fragmented landscape, we observed a moderate to high frequency (23.5-53%) of gene immigration, indicating that pollen movement beyond the boundaries of the small fragment can reach distances 41 km (i.e., the distance between the small studied population and the nearest pollen source). Gene flow by pollen dispersal beyond the edges of seemingly isolated forest fragments has been reported for several plant species, including species that are animal-pollinated (Nason and Hamrick, 1997;Dow and Ashley, 1998;Dick et al, 2003;Sato et al, 2006;Nazareno and Carvalho, 2009;Buschbom et al, 2011;Ottewell et al, 2012;Côrtes et al, 2013;Tambarussi, 2013;Saro et al, 2014).…”
Section: Gene Flowmentioning
confidence: 99%
“…Indeed, even in a highly fragmented landscape, we observed a moderate to high frequency (23.5-53%) of gene immigration, indicating that pollen movement beyond the boundaries of the small fragment can reach distances 41 km (i.e., the distance between the small studied population and the nearest pollen source). Gene flow by pollen dispersal beyond the edges of seemingly isolated forest fragments has been reported for several plant species, including species that are animal-pollinated (Nason and Hamrick, 1997;Dow and Ashley, 1998;Dick et al, 2003;Sato et al, 2006;Nazareno and Carvalho, 2009;Buschbom et al, 2011;Ottewell et al, 2012;Côrtes et al, 2013;Tambarussi, 2013;Saro et al, 2014).…”
Section: Gene Flowmentioning
confidence: 99%
“…Sato et al (2006) found low levels of genetic structure and attributed this to high levels of pollen and seed dispersal. Weak genetic structure may be the result of pollen and seed dispersal as well as post-recruitment mortality (Hardesty et al 2005).…”
Section: Population Differentiationmentioning
confidence: 99%
“…Windpollinated species are expected to have a higher genetic diversity and lower population differentiation than insect-pollinated species, as wind-dispersed pollen can travel great distances (Dow and Ashley 1998;Sato et al 2006). Salix sitchensis appears to be wind and insect-pollinated, with a higher proportion of wind pollination (Chapter 2).…”
Section: Gene and Genotypic Diversitymentioning
confidence: 99%
See 2 more Smart Citations